History of caesarean section - Zwierzyńska, Anna; Gruszka, Jakub; Janowski, Jacek; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2022)
Cesarean section is a obstetric procedure known since ancient times. It is mentioned in almost all ancient cultures. While until the 17th century it was performed mainly post mortem to retrieve an infant from the body of the deceased mother, today there are many indications for termination of pregnancy in this way. Literature provides references to earlier attempts to save the mother, but this happened only sporadically. The first record of a cc that both mother and child survived dates back to 1500. The development of science and medicine contributed to the dissemination and improvement of the methods used to extract a child by caesarean section. It was influenced by the development of operational, anesthetic and aseptic techniques. A milestone was the introduction of the Pfannenstiel – Kerr lower transverse incision method. Later, the Misgav-Ladach technique was introduced. Today, transverse incisions are most commonly used.